(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Solar power system should be frequently monitored for the optimum output and long-lasting efficiency. Internet of Things is an emerging technology that helps us in improving our lifestyle in an efficient and effective manner. Through internet of synchronized communications, it brings devices and external world closer. The laying of solar panels will definitely be far for the service provider and the housemates. So, this proposed project helps retrieve efficient power output from solar power supply system while monitoring for faults in the panel surface, connection error, dust accumulation and some other factors that stop efficient outcome of power. Here we frequently monitor various parameters like Voltage, current, temperature, humidity, and Light intensity through sensors and their data are reserved in cloud. It facilitates the user and service provider to check the output performance at any corner of the world. The inmates are facilitated to look up the performance output at each instance through LCD monitor attached to the solar mains also. In the event of low voltage production, an alert through mail is made to send intimating to check the panel performance in a short span. This helps in fast recovery and good efficiency of the system. Advancement of cloud technology plays a vital role for the credits.